Kıssa-i Kıran-ı Habeşi giriş-tenkitli metin-dizin cilt: 2 - Bulut, Yasemin (My University, 2009)
Bu çalışma tahminen Hicrî 6. (Miladî 12.) yüzyılda yaşamış olan İranlı yazar ’nin adlı eserinin, 15. yüzyılın sonlarında adı bilinmeyen bir mütercim tarafından başlıca üç bölümden oluşmaktadır: olan Giriş’te eserin aslının yazarının hayatı ve eserleri hakkında bilgi verilmiş; bu çalışmaya esas olan eserin nüshalarının tavsifi, yazıldığı dönem, tercüme niteliği, içeriği, dil ve imla özellikleri üzerinde durulmuştur. İkinci bölüm olan Metin’de eserin Topkapı Sarayı Müzesi Kütüphanesi Hazine 1613 ve Topkapı Sarayı Müzesi Kütüphanesi Ahmed III 3112 numaralarda kayıtlı nüshalarına dayanarak tenkitli metni ortaya konmuştur. Bu karşılaştırmanın sonunda transkripsiyonlu yeni bir metin oluşturulmuş ve nüsha farklılıkları dipnotlarda gösterilmiştir. Üçüncü bölüm Genel Dizin ile Özel İsimler Dizini’ni içermektedir. Genel dizinde kelimelerin eser içinde kazanmış oldukları mânâlarıyla verilmesine özen gösterilmiştir. Alıntı kelimelerin geldiği dil belirtilmiştir. Özel İsimler Dizini’nde, şahıs isimleri ve yer adları ayrı listelenmiştir. Tezin sonunda eserin Topkapı Sarayı Hazine 1613 nüshasının tıpkıbasımı verilmiştir. This thesis is on the Turkish translation of the book Dastan-ı Kıran-ı Hbaeşi by an Iranian author Ebu Tahir Muhammed bin Hasan bin Ali Musa Tarsusi or Tartusi who lived approximately in the 6th century of the Hegira (12th century of the Christian era) which was translated with a name of Kıssa-i Kıran-ı Habeşi by an anonymous translator at the end of the 15th century. The thesis consists of three chapters: Chapter 1 consists of the introduction part of the thesis. In this chapter, the stories of the author have been examined with a historical approach and a list of other studies is also provided in a cronological order. In addition, introduction of copies of Kıssa-i Kıran-ı Habeşi, the age in which it was written, the quality of translation, the content, language used and spelling qualities are examined. The following chapter, Chapter 2, is the next part of the thesis. In this chapter, the text is investigated in details based on the copies registered with the numbers Hazine 1613 and Ahmed III 3112 in Topkapı Palace Museum Library. After this comparison, a new text has been prepared with a transcription and the differences among the givencopies have also been mentioned in the footnotes. The General Index and the Index of Names are presented in Chapter 3. In this chapter, the meanings of the words are tried to be provided in their actual meanings. The source of the borrowing words are also mentioned. The names of the people and places are listed seperately in the Index of Names section. At the end of the thesis, a copy of the original text registered with a number Hazine 1613 in Topkapı Palace Museum Library has also been provided.
Keywords: Kıssa-i Kıran-ı Habeşi; Türk Dili